Impact modification of styrenic polymers with polyolefin acrylic polymers.
Patent Information
- Application Number
- JP2022520809
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Priority Date
- 2019-10-18
- Filing Date
- 2020-10-14
- Publication Date
- 2025-03-11
- Estimated Expiration
- 2040-10-14
Smart Images

Figure 0007644106000001 
Figure 0007644106000002 
Figure 0007644106000003
Abstract
Description
[Technical field]
[0001] The field of the invention is the impact modification of styrenic polymers. [Background technology]
[0002] Styrene-acrylonitrile (SAN) and other styrene-based copolymers have very attractive properties such as hardness, low density, high temperature and chemical resistance, and ease of processing. SAN copolymers are widely used in commercial products such as household goods, packaging, electrical appliances, automotive interior lenses, industrial battery cases, and medical components (Encyclopedia of Polymer Science and Technology, pp.174-203). Due to its inherent brittleness, SAN copolymers are often blended with rubber to enhance their impact resistance. Among other rubbers, SAN-grafted polybutadiene or poly(butyl acrylate), ethylene-vinyl acetate (EVA) copolymers, chlorinated polyethylene copolymers (CPE), and ethylene-propylene diene monomer (EPDM) polymers either grafted with SAN or blended with suitable EVA, or even silicone-based rubbers, have been used to modify the impact resistance of SAN.
[0003] When the rubber used for impact modification is butadiene based, the final blend of SAN and SAN grafted butadiene is called ABS, which is a well known material in the plastics industry and is used in many applications such as automotive parts including radiator grilles, headlight housings, mirror housings, etc., and in appliances, the second major application of ABS, this plastic is used in refrigerator doors and liners. Still, a major problem with ABS is its poor weatherability due to the use of butadiene in the rubber phase.
[0004] Poly(butyl acrylate)-based rubbers grafted with rigid shells are well known in the art. In particular, acrylonitrile-styrene-acrylate materials (ASA) consist of a core of butyl acrylate rubber grafted with a SAN shell and dispersed in a SAN matrix. Alternatively, the grafted rigid shell can be made of methyl methacrylate, MMA, or a copolymer of MMA with another monomer. With these materials, weather resistance is very high, but the impact resistance levels achieved are lower than those observed with ABS.
[0005] Another alternative to toughen SAN copolymers is to use polyolefin-based elastomers grafted with suitable monomers that make them compatible with SAN. Several examples of this methodology exist, such as EPDM, an ethylene-propylene-diene monomer rubber grafted with SAN itself, or ethylene-butene copolymer (EB) grafted with methyl methacrylate-acrylonitrile (MAN) copolymer (CN10 / 1684169(B)). These materials are generally known as acrylonitrile-ethylene-elastomer-styrene, or AES, and come in various versions, such as those with SAN-compatible copolymers added to facilitate dispersion and bonding of ungrafted EPDM or similar elastomers. There are some inconveniences with this approach, such as the grafting reaction being carried out in a solvent for EPDM-SAN materials, or the combination of a solvent-aqueous suspension for EB-MAN grafts. Processing variability can affect both grafting and compatibilization approaches.
[0006] One particular acrylic impact modifier (AIM) bimodal blend produces about 150 J / m at 35 wt% loading. ASA Geloyd GRXTWE270M shows 145 J / m using 40 wt% loading. Others have observed that EXL-2330 performs better than other acrylics in SAN with 25% AN (A Steenbrink, VM Litvinov and R J Gaymans, Polymer Vol. 39 No. 20, pp. 4817-4825, 1998).
[0007] KR2017 / 054642(A) discloses the use of ethylene-α-olefin copolymers emulsified by high speed homogenization and grafted with SAN. This modifier is useful for modifying the impact resistance of SAN while providing high gloss and good colorability, and good weatherability compared to ABS.
[0008] However, there remains a need for impact modifiers for styrenic polymers that provide both impact resistance and weatherability. Summary of the Invention
[0009] Disclosed herein is an impact modifier resin comprising an impact modifier and a matrix polymer resin. The impact modifier comprises particles of a crosslinked polyolefin elastomer having at least one (meth)acrylic monomer grafted to the crosslinked polyolefin elastomer particles. The matrix polymer resin comprises a styrene-based polymer.
[0010] Articles including the impact modified resins are also disclosed. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0011] As used herein, the following terms have the definitions specified, unless the context clearly indicates otherwise.
[0012] Hydrocarbons are compounds that contain only atoms of hydrogen and carbon. Atoms other than carbon and hydrogen are "hetero" atoms. Chemical groups that contain one or more heteroatoms are "hetero" groups.
[0013] As used herein, a "polymer" is a relatively large molecule that is composed of the reaction product of smaller chemical repeating units. Polymers can have structures that are linear, branched, star-shaped, looped, hyperbranched, crosslinked, or combinations thereof, and polymers can have a single type of repeating unit ("homopolymer") or they can have two or more types of repeating units ("copolymer"). Copolymers can have different types of repeating units arranged randomly, sequentially, in blocks, in other arrangements, or in any mixture or combination thereof. A polymer has a weight average molecular weight of 1,000 Daltons or more. A polymer that is sufficiently crosslinked to be insoluble in any solvent is considered to have an infinite molecular weight.
[0014] Molecules that can react with each other to form repeat units of a polymer are known herein as "monomers." The repeat units so formed are known herein as "polymerized units" of the monomer.
[0015] An olefin monomer is a monomer that is a hydrocarbon that has one or more carbon-carbon double bonds and does not contain an aromatic ring.
[0016] A polymer having more than 50% by weight of polymerized units of olefin monomers is a polyolefin. A vinyl aromatic monomer is a vinyl monomer in which one or more of R1, R2, R3, and R4 contain one or more aromatic rings. (Meth)acrylate means acrylate or methacrylate. (Meth)acrylic means acrylic or methacrylate. A (meth)acrylic monomer is a monomer selected from acrylic acid, methacrylic acid, alkyl esters thereof, substituted alkyl esters thereof, amides thereof, N-substituted amides thereof, acrylonitrile, methacrylonitrile, and mixtures thereof. The substituents can be, for example, hydroxyl groups, alkyl groups, aromatic groups, groups containing non-aromatic carbon-carbon double bonds, or other groups, or combinations thereof. A (meth)acrylic polymer is a polymer having more than 50% by weight of polymerized units of (meth)acrylic monomers.
[0017] Alpha-olefins are hydrocarbons with three or more carbon atoms and with exactly one carbon-carbon double bond located at a terminal carbon atom. That is, in alpha-olefins, at least one of the two carbon atoms of the carbon-carbon double bond also has two hydrogen atoms attached to it. Dienes are hydrocarbons with exactly two carbon-carbon double bonds. Dienes may be conjugated or non-conjugated.
[0018] Polyolefins made exclusively from hydrocarbon monomers are considered to be hydrocarbons, even if a small number of hetero groups are attached to the polyolefin as fragments from initiators and / or chain transfer agents. In hydrocarbon polyolefins, the molar ratio of heteroatoms to polymerized units of all monomers is 0.001:1 or less. Polyolefins that are not hydrocarbons are non-hydrocarbon polyolefins.
[0019] As used herein, a cross-linking agent is a compound that has two or more carbon-carbon double bonds.
[0020] A dispersion is a collection of particles distributed throughout a continuous liquid medium. A continuous liquid medium is an aqueous medium if the liquid medium is 50% or more by weight water, based on the weight of the liquid medium. A dispersion has a "solids" content that is determined by weighing the dispersion (WDISP), then drying the dispersion on an infrared moisture balance at 150°C until the weight stabilizes, then determining the weight of the dry residue (WDRY), then Solids=100*WDRY / WDISP.
[0021] Initiators are compounds that, when exposed to initiating conditions, generate radical moieties capable of initiating free radical polymerization. The nature of the initiating conditions varies from initiator to initiator. In some examples, thermal initiators generate radical moieties when heated to a high enough temperature, and photoinitiators generate radical moieties when exposed to radiation of a short enough wavelength and high enough intensity. As another example, redox initiators are a pair of molecules that react together in an oxidation / reduction reaction to generate radical moieties, and initiating conditions are obtained when both members of the pair are present and able to react with each other.
[0022] Emulsion polymerization is a process in which monomer emulsion droplets, a water-soluble initiator, and optionally seed particles are present in an aqueous medium. During emulsion polymerization, monomer molecules migrate from the monomer emulsion droplets to particles where polymerization takes place, which may be separate particles formed during polymerization or seed particles, or a combination thereof.
[0023] A polymer may be characterized by its glass transition temperature (Tg), which is measured by differential scanning calorimetry (DSC) using the inflection point method at a scan rate of 10° C. / min.
[0024] A collection of particles may be characterized by a volume average diameter.
[0025] Ratios are characterized herein as follows: for example, when a ratio is said to be 5:1 or greater, the ratio can be 5:1 or 6:1 or 100:1, but not 4:1. Stated generally, this characteristic is when a ratio is said to be X:1 or greater, the ratio is Y:1, where Y is X or greater. Similarly, for example, when a ratio is said to be 2:1 or less, it means that the ratio can be 2:1 or 1:1 or 0.001:1, but not 3:1. Stated generally, this characteristic is when a ratio is said to be Z:1 or less, the ratio is W:1, where W is Z or less.
[0026] A first aspect of the present invention relates to an impact modified resin comprising an impact modifier and a matrix polymer resin, wherein the impact modifier comprises particles of crosslinked polyolefin elastomer, one or more (meth)acrylic monomers are grafted to the crosslinked polyolefin elastomer particles, and the matrix polymer resin comprises a styrenic polymer.
[0027] Preferably, the crosslinked polyolefin elastomer particles form a core and the one or more (meth)acrylic monomers grafted to the crosslinked polyolefin elastomer particles form at least partially a shell around the core.
[0028] The impact modifier is preferably prepared by dispersing a polyolefin elastomer using an extrusion-emulsion process, such as the processes disclosed in WO 2019 / 133168 and U.S. Pat. No. 10,131,775, the disclosures of which are incorporated herein by reference.
[0029] Preferably, the volume average particle diameter of the dispersion of polyolefin elastomer particles is in the range of 50 nm to 2500 nm. The polyolefin elastomer particles can be 100 nm or more, more preferably 150 nm or more, more preferably 200 nm or more, or more preferably 250 nm or more. Preferably, the volume average particle diameter of the dispersion of primary polyolefin particles is 2000 nm or less, more preferably 1500 nm or less, more preferably 1000 nm or less, or more preferably 800 nm or less.
[0030] The high shear mechanical dispersion process may allow the polyolefin elastomer particles to be formed in an aqueous phase without the use of solvents. Furthermore, this process allows the size of the polyolefin elastomer particles to be controlled.
[0031] The amount of total polyolefin in the initial polyolefin elastomer particles is 50% by weight or more, more preferably 60% by weight or more, more preferably 70% by weight or more, more preferably 80% by weight or more, based on the total solids weight of the dispersion. The amount of total polyolefin polymer in the initial polyolefin particles is preferably 98% by weight or less, more preferably 96% by weight or less, based on the total solids weight of the dispersion.
[0032] The initial polyolefin elastomer particles preferably have a Tg of 50° C. or less, more preferably 30° C. or less, more preferably 15° C. or less, more preferably 0° C. or less, more preferably −15° C. or less.
[0033] The polyolefin elastomer may be selected from polyolefin homopolymers and copolymers. The polyolefin elastomer may comprise a single polyolefin elastomer, a blend of two or more polyolefin elastomers, or a blend of one or more polyolefin elastomers with one or more additional polymers.
[0034] Examples of polyolefins include homopolymers and copolymers of one or more alpha-olefins such as ethylene, propylene, 1-butene, 3-methyl-1-butene, 4-methyl-1-pentene, 3-methyl-1-pentene, 1-heptene, 1-hexene, 1-octene, 1-decene, and 1-dodecene, typically represented by polyethylene, polypropylene, poly-1-butene, poly-3-methyl-1-butene, poly-3-methyl-1-pentene, poly-4-methyl-1-pentene, ethylene-propylene copolymers, ethylene-1-butene copolymers, and propylene-1-butene copolymers; conjugated or non-conjugated, typically represented by ethylene-butadiene copolymers and ethylene-ethylidenenorbornene copolymers. Polyolefins such as copolymers of alpha-olefins with dienes; and copolymers of two or more alpha-olefins with conjugated or non-conjugated dienes, typically represented by ethylene-propylene-butadiene copolymer, ethylene-propylene dicyclopentadiene copolymer, ethylene-propylene-1,5-hexadiene copolymer, and ethylene propylene-ethylidene norbornene copolymer; ethylene-vinyl compound copolymers such as ethylene-vinyl acetate copolymer, ethylene-vinyl alcohol copolymer, ethylene-vinyl chloride copolymer, ethylene acrylic acid or ethylene-(meth)acrylic acid copolymer, and ethylene-(meth)acrylate copolymer. These resins can be used alone or in combination of two or more.
[0035] In selected embodiments, the polyolefin may comprise one or more polyolefins selected from the group consisting of, for example, ethylene-alpha olefin copolymers, propylene-alpha olefin copolymers, and olefin block copolymers. In particular, in selected embodiments, the polyolefin may comprise one or more non-polar polyolefins.
[0036] In certain embodiments, polyolefins such as polypropylene, polyethylene, their copolymers, and their blends, as well as ethylene-propylene-diene terpolymers may be used.In some embodiments, exemplary olefin polymers include the homogeneous polymers described in U.S. Pat. No. 3,645,992; high density polyethylene (HDPE) described in U.S. Pat. No. 4,076,698; heterogeneously branched linear low density polyethylene (LLDPE); heterogeneously branched linear ultra-low density polyethylene (ULDPE); homogeneously branched linear ethylene / alpha-olefin copolymers; homogeneously branched substantially linear ethylene / alpha-olefin polymers, such as those prepared by the processes disclosed in U.S. Pat. Nos. 5,272,236 and 5,278,272 (the disclosures of which are incorporated herein by reference); and high pressure free radical polymerization ethylene polymers and copolymers, such as low density polyethylene (LDPE) or ethylene-vinyl acetate polymer (EVA).
[0037] In one particular embodiment, the polyolefin is a propylene / alpha-olefin copolymer characterized in having substantially isotactic propylene sequences. "Substantially isotactic propylene sequences" refers to sequences that are 13 It means having an isotactic triad (mm) of greater than about 0.85, alternatively greater than about 0.90, yet alternatively greater than about 0.92, and yet alternatively greater than about 0.93, as measured by C NMR. Isotactic triads are well known in the art and are described, for example, in U.S. Pat. No. 5,504,172 and WO 00 / 01745, which disclose isotactic triads of greater than about 0.85, alternatively greater than about 0.90, and yet alternatively greater than about 0.92, as measured by C NMR. Isotactic triads are well known in the art and are described, for example, in U.S. Pat. No. 5,504,172 and WO 00 / 01745, which disclose isotactic triads of greater than about 0.85, alternatively greater than about 0.90, and yet alternatively greater than about 0.93, as measured by C NMR. 13 It refers to the isotactic arrangement of triad units in a copolymer molecular chain as determined by C NMR spectroscopy. Propylene / alpha-olefin copolymers contain units derived from propylene and polymer units derived from one or more alpha-olefin comonomers. Exemplary comonomers utilized in the production of propylene / alpha-olefin copolymers are C2 and C 4 ~C 10 Alpha-olefins, e.g., C 2 , C 4 , C 6 , and C 8 It is an alpha-olefin.
[0038] The olefin copolymer may have a melt flow rate in the range of 1 to 1500 g / 10 min, measured according to ASTM D-1238 (190° C. / 2.16 Kg). All individual values and subranges from 1 to 1500 g / 10 min are included herein and disclosed herein, for example, the melt flow rate can be from a lower limit of 1 g / 10 min, 2 g / 10 min, 3 g / 10 min, 4 g / 10 min, 5 g / 10 min, 100 g / 10 min, 200 g / 10 min, 500 g / 10 min, 800 g / 10 min, 1000 g / 10 min, 1300 g / 10 min, or 1400 g / 10 min to an upper limit of 1500 g / 10 min, 1250 g / 10 min, 1000 g / 10 min, 800 g / 10 min, 500 g / 10 min, 100 g / 10 min, 50 g / 10 min, 40 g / 10 min, and 30 g / 10 min. For example, the propylene / alpha-olefin copolymer may have a melt flow rate ranging from 1 to 1500 g / 10 min, or from 1 to 500 g / 10 min, or from 500 to 1500 g / 10 min, or from 500 to 1250 g / 10 min, or from 300 to 1300 g / 10 min, or from 5 to 30 g / 10 min.
[0039] The olefin copolymers have a molecular weight distribution (MWD), defined as the weight average molecular weight divided by the number average molecular weight (Mw / Mn), of less than or equal to 3.5, alternatively less than or equal to 3.0, or further alternatively from 1.8 to 3.0. Such olefin copolymers are commercially available from The Dow Chemical Company under the trade names VERSIFY™ and ENGAGE™, or from ExxonMobil Chemical Company under the trade names VISTAMAXX™ and EXACT™.
[0040] In other selected embodiments, olefin block copolymers, such as ethylene multi-block copolymers, such as those described in WO 2005 / 090427 and U.S. Patent Application Publication No. 2006 / 0199930, which are incorporated by reference to the extent that they describe such olefin block copolymers, may be used as polyolefins. Such olefin block copolymers are ethylene / α-olefin interpolymers, (a) has a Mw / Mn of about 1.7 to about 3.5, at least one melting point Tm (in degrees Celsius), and a density d (in grams per cubic centimeter), the numerical values of Tm and d corresponding to the following relationship: Tm>-2002.9+4538.5(d)-2422.2(d) 2 (b) having a Mw / Mn of about 1.7 to about 3.5 and characterized by a heat of fusion ΔH (in J / g) and a delta mass ΔT (in degrees Celsius) defined as the temperature difference between the highest DSC peak and the highest CRYSTAF peak, the values of ΔT and ΔH having the following relationship: If ΔH is greater than zero and up to 130 J / g, then ΔT>-0.1299(ΔH)+62.81; If ΔH is greater than 130J / g, ΔT≧48℃ The CRYSTAF peak is determined using at least 5 percent of the cumulative polymer, and if less than 5 percent of the polymer has a discernible CRYSTAF peak, the CRYSTAF temperature is 30° C., or (c) characterized by an elastic recovery Re (in percent) at 300 percent strain and one cycle, as measured on a compression molded film of the ethylene / α-olefin interpolymer, and having a density d (in grams per cubic centimeter), wherein the ethylene / α-olefin interpolymer is substantially free of crosslinked phases, the numerical values of Re and d satisfy the following relationship: Re>1481-1629(d) (d) having a molecular fraction that, when fractionated using TREF, elutes between 40° C. and 130° C., the fraction being characterized by having a molar comonomer content that is at least 5 percent higher than a comparable random ethylene interpolymer fraction eluting between the same temperatures, the comparable random ethylene interpolymer having the same comonomer and a melt index, density, and molar comonomer content (on a whole polymer basis) within 10 percent of the ethylene / α-olefin interpolymer; or (e) An ethylene / α-olefin interpolymer having a storage modulus at 25° C., G′(25° C.), and a storage modulus at 100° C., G′(100° C.), the ratio of G′(25° C.) to G′(100° C.) ranging from about 1:1 to about 9:1.
[0041] Such olefin block copolymers, e.g., ethylene / α-olefin interpolymers, can also be (a) a molecular fraction that, when fractionated using TREF, elutes between 40° C. and 130° C., the fraction being characterized by a block index of at least 0.5 and at most about 1, and a molecular weight distribution, Mw / Mn, of greater than about 1.3; or (b) have an average block index greater than zero and up to about 1.0, and a molecular weight distribution, Mw / Mn, of greater than about 1.3.
[0042] In certain embodiments, the polyolefin may include one or more polar polyolefins, for example, having polar groups as either comonomers or grafted monomers. Exemplary polar polyolefins include, but are not limited to, ethylene-acrylic acid (EAA) and ethylene-methacrylic acid copolymers, such as those available under the trade names PRIMACOR™ available from The Dow Chemical Company, NUCREL™ available from EI DuPont de Nemours, and ESCOR™ available from ExxonMobil Chemical Company, and described in U.S. Patents 4,599,392, 4,988,781, and 5,938,437, each of which is incorporated herein by reference in its entirety. Other exemplary base polymers include, but are not limited to, ethylene ethyl acrylate (EEA) copolymers, ethylene methyl methacrylate (EMMA), and ethylene butyl acrylate (EBA).
[0043] In one embodiment, the polar polyolefin may be selected from the group consisting of ethylene-acrylic acid (EAA) copolymers, ethylene-methacrylic acid copolymers, and combinations thereof, and the stabilizer may comprise, for example, a polar polyolefin selected from the group consisting of ethylene-acrylic acid (EAA) copolymers, ethylene-methacrylic acid copolymers, and combinations thereof, provided that the base polymer may have a lower acid number than the stabilizer, for example, as measured according to ASTM D-974.
[0044] Polyolefins that are copolymers can be statistical copolymers, block copolymers, graft copolymers, copolymers with other structures, or mixtures thereof, with statistical copolymers being preferred.
[0045] The polyolefin elastomer particles are then crosslinked. Preferred crosslinkers are selected from polyolefins having carbon-carbon double bonds ("polyolefin crosslinkers") and compounds having a molecular weight of 500 or less and having two or more carbon-carbon double bonds ("monomeric crosslinkers"). Among the polyolefin crosslinkers, homopolymers and copolymers containing one or more polymerized units of dienes are preferred. Among the monomeric crosslinkers, those having two or more carbon-carbon double bonds, more preferably three or more carbon-carbon double bonds, are preferred. Suitable monomeric crosslinkers include butanediol diacrylate, butanediol dimethacrylate, ethylene glycol diacrylate, ethylene glycol dimethacrylate, divinylbenzene, diethylene glycol diacrylate, diethylene glycol dimethacrylate, diallyl maleate, allyl methacrylate, diallyl phthalate, triallyl phthalate, trimethylolpropane triacrylate, trimethylolpropane trimethacrylate, triallyl isocyanurate, and 1,3,5,7-tetravinyl-1,3,5,7-tetramethylcyclotetrasiloxane, blends thereof, and combinations of two or more thereof.
[0046] The amount of crosslinking agent is preferably 0.5% by weight or more, more preferably 1% by weight or more, more preferably 1.5% by weight or more, based on the total solids weight of the dispersion of the initial polyolefin particles. The amount of crosslinking agent is preferably 20% by weight or less, more preferably 15% by weight or less, based on the total solids weight of the dispersion of the initial polyolefin particles.
[0047] The dispersion of polyolefin elastomer particles may also contain one or more surfactants. Preferred surfactants are anionic surfactants having a hydrocarbon group of 8 or more carbon atoms and an anionic group. The hydrocarbon group may be linear, branched, aromatic, or a combination thereof, and is preferably a linear hydrocarbon group. The anionic group is a chemical group that is negatively charged in water at pH 7. Preferred anionic groups are phosphate, phosphonate, carboxylate, sulfate, and sulfonate groups, and more preferably, sulfate groups. Preferred anionic surfactants also contain the group -(CH2CHO)n-. If the group -(CH2CHO)n- is present, it is preferably attached to a sulfate group. The index n is 1 or more, preferably 2 or more. The index n is preferably 20 or less, more preferably 15 or less, more preferably 10 or less, more preferably 6 or less, more preferably 4 or less, and more preferably 3 or less.
[0048] The amount of surfactant in the dispersion of polyolefin elastomer particles is preferably 0.5% by weight or more, more preferably 1% by weight or more, more preferably 2% by weight or more, more preferably 3% by weight or more, based on the total solids weight of the dispersion. The amount of surfactant in the dispersion of polyolefin elastomer particles is preferably 10% by weight or less, more preferably 8% by weight or less, more preferably 6% by weight or less, more preferably 4% by weight or less, based on the total solids weight of the dispersion.
[0049] Preferably, the crosslinked polyolefin particles have a volume average particle diameter of 100 nm or more, more preferably 150 nm or more, more preferably 200 nm or more, more preferably 250 nm or more. Preferably, the crosslinked polyolefin particles have a volume average particle diameter of 2000 nm or less, more preferably 1000 nm or less, more preferably 750 nm or less, more preferably 500 nm or less.
[0050] One or more (meth)acrylic monomers are grafted to the crosslinked polyolefin elastomer particles to form the composition polymer composition. The (meth)acrylic monomers can be grafted to the polyolefin elastomer particles by emulsion polymerization. Preferably, the grafted (meth)acrylic monomers form at least a partial acrylic shell on the core of the crosslinked polyolefin elastomer particles.
[0051] Preferably, the (meth)acrylic monomer is a C acrylate such as, for example, methyl (meth)acrylate, ethyl (meth)acrylate, propyl (meth)acrylate, butyl (meth)acrylate, 2-ethylhexyl acrylate, hexyl acrylate, ethylhexyl methacrylate, stearyl acrylate, benzyl acrylate, cyclohexyl methacrylate, isobornyl methacrylate, tetrahydrofurfuryl methacrylate, cyclopentyl methacrylate, trifluoroethyl methacrylate, hydroxyethyl methacrylate, dicyclopentadienyl methacrylate, and combinations thereof. 1 ~C 18 (meth)acrylate. More preferably, the (meth)acrylic monomer comprises a combination of methyl (meth)acrylate and butyl (meth)acrylate monomers, and even more preferably, a combination of methyl methacrylate and butyl acrylate monomers.
[0052] The (meth)acrylic monomers can be functionalized, non-functionalized, or a combination thereof. Examples of functionalized (meth)acrylic monomers include, but are not limited to, acrylic acid, methacrylic acid, glycidyl methacrylate, allyl methacrylate, hydroxyethyl methacrylate, and acrylamide.
[0053] Preferably, the Tg of the grafted (meth)acrylic monomer is greater than 50°C, more preferably greater than 75°C.
[0054] The weight ratio of polyolefin elastomer to (meth)acrylic monomer in the composite polymer composition is preferably in the range of 50:50 to 90:10, more preferably 60:40 to 85:15, and even more preferably 70:30 to 80:20.
[0055] One or more crosslinking agents and / or graft linking agents may optionally be added to the emulsion polymerization. Exemplary crosslinking agents include, for example, divinylbenzene; vinyl group-containing monomers, including triallyl (iso)cyanurate, and trimethyl trimellitate; (poly)alkylene glycol di(meth)acrylate compounds, including ethylene glycol dimethacrylate (EGDMA), diethylene glycol dimethacrylate, 1,6-hexanediol di(meth)acrylate, (poly)ethylene glycol di(meth)acrylate, (poly)propylene glycol di(meth)acrylate, (poly)tetramethylene glycol di(meth)acrylate, pentaerythritol tetra(meth)acrylate, pentaerythritol tri(meth)acrylate, pentaerythritol di(meth)acrylate, trimethylolpropane tri(meth)acrylate, dipentaerythritol hexa(meth)acrylate, dipentaerythritol penta(meth)acrylate, and glycerol tri(meth)acrylate, and mixtures and combinations thereof. Exemplary graft linking agents include, for example, allyl methacrylate, diallyl maleate, and allyl acryloxypropionate.
[0056] The particles may be spray dried or freeze dried to form the impact modifier.
[0057] The impact modifier may be added to a matrix polymer resin to form an impact modified resin. Preferably, the matrix polymer resin is a styrene-based polymer. Even more preferably, the styrene-based polymer is a styrene-acrylonitrile copolymer (SAN). SAN contains 60-90% by weight of polymerized units of styrene and 10-40% by weight of polymerized units of acrylonitrile, for example, 70-80% by weight of polymerized units of styrene and 20-30% by weight of acrylonitrile. In a SAN polymer, the sum of the weight percentages of styrene and acrylonitrile is 70% or more. For example, polymerized units of other monomers such as alkyl (meth)acrylate monomers may be present.
[0058] Preferably, the impact modifier is present in the impact modified resin in an amount ranging from 20 to 50% by weight, based on the total weight of the impact modifier and the matrix polymer resin. More preferably, the impact modifier is present in the impact modified resin in an amount ranging from 25 to 45% by weight, based on the total weight of the impact modifier and the matrix polymer resin. Even more preferably, the impact modifier is present in the impact modified resin in an amount ranging from 30 to 40% by weight, based on the total weight of the impact modifier and the matrix polymer resin.
[0059] The impact modified resin may further include one or more additives selected from colorants (e.g., pigments and / or dyes), UV and / or light stabilizers, processing aids, antioxidants, flame retardants and / or smoke suppressants, heat stabilizers, and lubricants. These ingredients are known in the art and may be used in accordance with conventional practices.
[0060] The impact-modified resin can be formed by any method. Preferably, the mixture of the matrix polymer and the impact modifier particles is heated to a molten state, and the mixture is subjected to mechanical shear. For example, the powder of the matrix polymer can be mixed with the impact modifier particles in powder form at a temperature low enough so that the matrix polymer does not melt, and then the mixture of the powder and the powder can be fed into an extruder, which heats the mixture to form a melt and applies shear to the mixture. As another example, the powder of the matrix polymer and the impact modifier particles in powder form can be fed separately into an extruder, which then provides heat and shear. It is contemplated that the mechanical shear will intimately mix the polymer particles with the resin polymer, resulting in the powder particles breaking apart, and then the individual polymer particles are distributed in the matrix polymer.
[0061] The impact modified resins may be used to form articles such as automobile parts including radiator grilles, headlight housings, mirror housings, and the like, and appliance parts including refrigerator doors and liners. EXAMPLES
[0062] Polyolefin elastomer cores (POD or POD seeds) were prepared from an elastomer (Engage™ 8842, The Dow Chemical Company) extruded into an aqueous phase containing surfactants and other stabilizers as listed in Table 1 below. [Table 1]
[0063] Polyolefin acrylic modifiers (POA) were produced by first crosslinking the elastomeric core particles. Triallyl isocyanurate (TAIC) was used for that purpose. A rigid shell made from methyl methacrylate / butyl acrylate in a weight ratio of 98 / 2 was grafted onto the elastomeric core particles. The core to shell ratio was 75-80 weight percent core and 25-20 weight percent shell, as detailed in Table 2 below. [Table 2]
[0064] The performance was evaluated by preparing blends of SAN and modifier in a two-roll mill by grinding for 5 minutes at 170° C. and molding for 4 minutes at 180° C. The SAN was a 78 / 22 styrene-acrylonitrile copolymer.
[0065] Table 3 shows the initial results obtained at 30 weight percent loading of modifier. All modifiers enhanced the impact strength of SAN (PN-128100, 78 / 22 styrene-acrylonitrile copolymer) at room temperature (notched Izod impact according to ASTM 256), but both POA core / shells according to the invention performed much better. Comparative Example C1 is SAN without modifier. Comparative Examples C2 and C3 contain all acrylic impact modifiers. Examples E1 and E2 contain impact modifiers POA-11c and POA-13 as described in Table 2 above. [Table 3]
[0066] Table 4 below shows follow-up experiments comparing a butadiene-based ABS type modifier, Blendex 338 from Galata Chemicals, with two different types of POA, as well as MBS and another acrylic of SAN (78 / 22 styrene-acrylonitrile, AS128 from Chimei). Comparative Example C4 used Blendex 338 as the modifier. Comparative Example C5 used PARALOID EXL-2668 as the modifier. Example E3 used ENGAGE™ 8842 core with 80 / 20 ratio MMA / BA shell as the modifier. Example E4 used POA-28B from Table 2 above as the modifier. Comparative Example C6 used Kane Ace™ FM-40 from Kaneka as the modifier. Comparative Example C7 used PARALOID™ KM-355P from The Dow Chemical Company as the modifier. Example E5 used a blend of two different modifiers, namely PARALOID™ KM-355P and POA-28B in a 50 / 50 weight ratio. The loading used was 35 wt%, which is more typical for ABS or ASA materials. In previous experiments, some premature hardening of the blend was observed when the molten mass was removed from the two-roll mill and placed in the pressing die, so the temperature processing and molding conditions were increased by 10° C. in this case to 185° C. and 195° C., respectively.
[0067] Again, the POA core / / shell provided higher impact resistance than any other modifier tested. In contrast, POA-28B, also based on a different α-olefin, did not provide comparably high impact performance, likely due to the larger particle size. Furthermore, bimodal blends of the modifier with a smaller particle size acrylic core / / shell (KM-355P) (using a 1:1 blend ratio by weight) did not provide the synergistic effect that SAN is known to exhibit. [Table 4]
[0068] Table 5 below shows a comparison of conventionally used SAN impact modifiers (Comparative Examples C8-C11) with Example E6, an example according to the invention. Comparative Example C8 used an industry standard impact modifier, MRC SX006 from Mitsubishi Chemical, which is a silicone-butyl acrylate-styrene-acrylonitrile composition. Comparative Example C9 used KLM-6930-1 with 2.5% DC52 from The Dow Chemical Company as the modifier. Comparative Example C10 used Kane Ace™ FM-40 from Kaneka as the modifier. Comparative Example C11 used PARALOID™ KM-357P from The Dow Chemical Company as the modifier. Example E6 is an impact modifier according to the present invention having a core formed of Engage 8137 / licocene 4351 / Retain 3000 / sodium-oleate / Empicol ESB / TAIC in a ratio of 80 / 5 / 10 / 1.5 / 1.5 / 2 with a MMA / BA shell of 98 / 2, a core:shell ratio of 80:20, and a particle size of 250 nm. The loading used was 40% by weight of the impact modifier of SAN. The performance was evaluated by preparing a blend of SAN and modifier in a two-roll mill by grinding at 170°C for 5 minutes and molding at 180°C for 4 minutes. The SAN was a 78 / 22 styrene-acrylonitrile copolymer. [Table 5]
Claims
1. 1. An impact modified resin comprising an impact modifier and a matrix polymer resin, wherein the impact modifier comprises particles of a crosslinked polyolefin elastomer, the polyolefin elastomer being selected from the group consisting of ethylene homopolymer, ethylene / α-olefin copolymer, ethylene / α-olefin block copolymer, propylene homopolymer, propylene / α-olefin copolymer, and propylene / α-olefin block copolymer, a combination of methyl methacrylate and butyl acrylate is grafted to the particles of the crosslinked polyolefin elastomer, and the matrix polymer resin is a styrene-acrylonitrile copolymer.
2. 10. The impact modified resin of claim 1, wherein the polyolefin elastomer comprises a first polyolefin elastomer and at least one additional component selected from an additional polyolefin elastomer, a random copolymer, and a block copolymer.
3. 3. The impact modified resin of claim 1 or 2, wherein the polyolefin elastomer is selected from ethylene-octene copolymers and ethylene-butene copolymers.
4. 4. The impact modified resin of any one of claims 1 to 3, wherein the impact modifier is present in an amount in the range of 20 to 50 weight percent, based on the total weight of the impact modifier and the matrix polymer resin.
5. An article comprising an impact-modified resin according to any one of claims 1 to 4.
Citation Information
Patent Citations
Rubber-modified thermoplastic resin and its composition
JP1999130826A
Isobutylene-based rubber particle, graft copolymer particle and resin composition containing the same particle
JP1999140250A
Method for preparing polyolefin-acrylic particles
WO2019133168A1
Method for modifying polycarbonate blends
WO2019133197A1